Evidence for a B-s(0)pi(+/-) State - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Amer Physical Soc, 2016)
We report evidence for a narrow structure, X(5568), in the decay sequence X(5568) -> B-s(0)pi(+/-), B-s(0) -> J/psi phi, J/psi -> mu(+)mu(-), phi -> K+K-. This is evidence for the first instance of a hadronic state with valence quarks of four different flavors. The mass and natural width of this state are measured to be m = 5567.8 +/- 2.9(stat)(-1.9)(+0.9) (syst) MeV/c(2) and Gamma = 21.9 +/- 6.4(stat)(-2.5)(+5.0) (syst) MeV/c(2). If the decay is X(5568) -> B-s*pi(+/-). B-s(0)gamma pi(+/-) with an unseen gamma, m(X(5568)) will be shifted up by m(B-s*) - m(B-s(0)) similar to 49 MeV/c(2). This measurement is based on 10.4 fb(-1) of p (p) over bar collision data at root s = 1.96 TeV collected by the D0 experiment at the Fermilab Tevatron collider.